2014
DOI: 10.1002/cta.2019
|View full text |Cite
|
Sign up to set email alerts
|

Design of novel efficient adder and subtractor for quantum‐dot cellular automata

Abstract: Summary Quantum‐dot cellular automata (QCA) is one of the new emerging technologies being investigated as an alternative to complementary metal oxide semiconductor technology. This paper proposes optimized one‐bit full adder (FA) for implementation in QCA. The fault effects at the proposed FA outputs due to the missing cell defects are analyzed, and the test vectors for detection of all faults are identified. Also, the efficient designs of one‐bit full subtractor (FS), one‐bit FA/FS and four‐bit carry flow add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 19 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…The fault tolerance for the sum output and carry output are 17.94% and 92.30%, respectively in [25]. Hayati and Rezaei [21] have proposed 1-bit FA that utilizes three 3-input MGs and one IG. This 1-bit FA has 0.02 µm 2 area, 38 QCA cells and two clock phases delay.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The fault tolerance for the sum output and carry output are 17.94% and 92.30%, respectively in [25]. Hayati and Rezaei [21] have proposed 1-bit FA that utilizes three 3-input MGs and one IG. This 1-bit FA has 0.02 µm 2 area, 38 QCA cells and two clock phases delay.…”
Section: Related Workmentioning
confidence: 99%
“…This 1-bit FA has 0.02 µm 2 area, 38 QCA cells and two clock phases delay. The fault tolerance for the sum output and the carry output are 12.12% and 48.48%, respectively in [21]. Kianpour et al [22] have presented 1-bit FA that utilizes three 3-input MGs and one IG.…”
Section: Related Workmentioning
confidence: 99%
“…Full‐adders are considered as one of the most important and most widely used digital computing circuitry blocks . However, fault‐tolerant full‐adders in QCA have not been addressed well.…”
Section: Proposed Fault‐tolerant Full‐addersmentioning
confidence: 99%
“…Information is reassigned via columbic exchanges between the fundamental elements (cells) instead of electrical current . Up to now, extensive attempts has been made on the design of various digital circuits such as multipliers, adders, multiplexers, and memories in QCA technology, but according to a study in Bahar et al, the high complexity of nanocircuit structures results in the need to design high fault‐tolerant structures. QCA technology encounters challenges like many defects that were first described in previous works .…”
Section: Introductionmentioning
confidence: 99%
“…Adders are the most important part of an arithmetic logic unit (ALU). Several studies have been reported about adders [7][8][9][10][11] and QCA serial adders [12][13][14]. Three designs of QCA serial adders have been presented in the previous studies [12][13][14].…”
Section: Introductionmentioning
confidence: 99%